Factors related to the decline and rebuilding of billfish stocks in the Atlantic and Indian oceans. (20th May 2017) - Sharma, Rishi; Pons, Maite; Martin, Sarah; Kell, Laurie; Walter, John; Lauretta, Matthew; Schirripa, Michael
Abstract: The article examines factors related to the decline and rebuilding of billfish stocks in the Atlantic and Indian oceans. Longline effort has declined over the last 10–15 years in both oceans. This decline in fishing pressure has led to the recovery of some stocks, but some species that are caught incidentally in industrial longline fisheries remain overexploited. Using a simple moving average technique on fishing mortality trajectories, we estimated a threshold effort size of 240 million hooks for the Atlantic Ocean and 364 million hooks for the Indian Ocean where stocks start experiencing overfishing. In addition, we highlight differences in the economic characteristics of the major fleets catching billfish in the two oceans and discuss how this may be associated with differences in management, enforcement, and stock rebuilding.